Gestalt Counseling Effectiveness with Engineering Techniques to Increase Self-Consideration in Learning Process - Munandar, Arief; Dantes, Nyoman; Tirka, Wayan (Department of Guidance and Counseling, FIP, Undiksha, 2017)
Confidence is important to be possessed by students through the learning process, students who have low self-confidence will be less optimal in developing ability. This study aims to determine the effectiveness of gestalt counseling with the technique around to improve confidence in the learning process in students of class XI MIA 4 SMA Negeri 1 Singaraja academic year 2016/2017. This type of research is pre-experimental with one group pretest-posttest design. Samples of research were six students selected through purposive sampling technique. Methods of data collection using a confident questionnaire that has been calculated the validity and reliability. The subjects from the study were students of class XI MIA 4 who had low self-esteem. Data analysis technique used is t-test statistical analysis technique. The results from the analysis, found that gestalt counseling with the technique of traveling can increase confidence. It is concluded from the analysis result, t count> table with significance level 5% (4, 38> 2, 015). The results from the analysis show that the hypothesis proposed in this study is acceptable. As the implication of this research is expected to be an alternative for counseling teachers in schools in improving student self-confidence.